Education and School Administration in the Nigerian History: The Colonial and Post-Colonial Characteristics - Maigida, Abdulrahman Yusuf (International Journal of Scientific Research and Management (IJSRM), 2018)
School administration in Nigeria is becoming much more issue that the society, the practitioners and all stakeholders discuss with concern, particularly with changing output of the system which some people condemn for reason, not far from retrogressive quality delivery. It is good to say that gone were those days that Nigeria was rated high in the practice of modern education. Today, it is clear that so many things are wrong. This paper is not to evaluate or assess how far the administration of school in Nigeria is faring, but tried to be historical in chronicling how we have come to where we are. The manifestations in the characteristics of school administration from colonial Nigeria, where colonial government was associated with educational administration while the missionaries and voluntary agencies with school administration. Now in the post-colonial period, where government is responsible entirely for educational administration with a number of regulatory agencies and private organisations/individuals, religious bodies and voluntary agencies are in the administration of schools. The paper used some templates from other advanced practice to further provide insights into what is obtainable in the contemporary Nigeria. The problems associated with school administration in general and specifically in Nigeria were highlighted, with some recommendations emphasizing that stakeholders should play by the rules